If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -4 = 6x + -22 Reorder the terms: -4 + 4x = 6x + -22 Reorder the terms: -4 + 4x = -22 + 6x Solving -4 + 4x = -22 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -4 + 4x + -6x = -22 + 6x + -6x Combine like terms: 4x + -6x = -2x -4 + -2x = -22 + 6x + -6x Combine like terms: 6x + -6x = 0 -4 + -2x = -22 + 0 -4 + -2x = -22 Add '4' to each side of the equation. -4 + 4 + -2x = -22 + 4 Combine like terms: -4 + 4 = 0 0 + -2x = -22 + 4 -2x = -22 + 4 Combine like terms: -22 + 4 = -18 -2x = -18 Divide each side by '-2'. x = 9 Simplifying x = 9
| 25b^2+80bf+64f^2= | | -5(x-3)+5=20 | | h(m)=20m+4800 | | x(2x+3)=44 | | 64=4X^2 | | 10x-7=35x+13 | | 3(m+9)=5(m-2) | | 0.5X^2=0 | | 5xc= | | 3s^2=8s | | 3x-32=7x+28 | | 89-6x=7x+24 | | 10-x-10-x-0.1-0.01x=0.05 | | x^2-25x+17=-9x+10 | | 4x^2-25x+17=-9x+10 | | y^2-24y-48=0 | | 5x^5=90 | | 6x^2+x-7=0 | | 4x+7=x+30 | | 8-9x=44 | | 4.5x-15=2.6x+18 | | 5x+72=13x | | d=4n-2 | | 15+12=q | | 20-g=6 | | -2(x-6)=-3(x+4)-9 | | 3+7=7+3 | | 4+f=13-2 | | 9-0.5y=2.5x | | 4f=13-2 | | v-14=26 | | 4k+44=10k-10 |